Interference, sunk investment, and the repurposing of radio spectrum. Issue 1 (2nd January 2020) - Randolph Beard, T.; Ford, George S.; Stern, Michael L.
ABSTRACT: In this article, we shed light on the optimal design of Commission rules and practices for addressing interference disputes. Since spectrum licenses produce no benefits without large and mostly sunk investments in communications networks, our focus is on investment incentives. We argue that the regulator's optimal interference policy would necessarily deal with different license holders differently when their sunk network investments vary. Our economic model dictates that license holders who have made little or no sunk investment in capital to generate benefits from their license would receive little relief under an optimal rule. On the other hand, those licensees with substantial sunk network investments would receive far more expansive treatment by the regulator.